VEGETATION AND CLIMATE HISTORY OF THE YANA RIVER LOWLAND, RUSSIA, DURING THE LAST 6400 YR - Andreev A.A; Klimanov V.A; Sulerzhitsky L.D (My University, 2001)
New pollen records and radiocarbon dates from two sites in the Yana River lowlands, Arctic Yakutia, Russia provide reconstruc-tions of vegetation and climate history of this region during the last 6400 yr. The #uctuations in pollen and spores re#ect the local hydrological events and regional climate changes. The data show that larch (Larix dahurica) forests with shrub alder (Alnus fruticosa) and dwarf birch (Betula exilis) dominated the area during the last 6400 yr BP. There is no evidence for tree-line #uctuations at the sites during the latter half of the Holocene. Climate reconstructions made by transfer function from one site show that the warmest time was between 6000 and 4500 yr BP. All climate #uctuations reconstructed at this site correspond well with regional climate changes.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен